1997
DOI: 10.1002/(sici)1097-0347(199701)19:1<63::aid-hed12>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Vascular leiomyoma of the superior turbinate: First reported case

Abstract: Background. Vascular leiomyoma is an uncommon smooth muscle tumor rarely found in the head and neck area. We report the first case arising from the superior turbinate of the nasal cavity.Methods. A case presentation, treatment, and review of the literature are discussed.Results. Twenty-one months after embolization and surgical resection, the patient is doing well, without evidence of recurrence.Conclusions. Vascular leiomyoma is a rare benign tumor of the nasal cavity, and surgical excision yields high cure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…1 According to the literature, the most common symptoms are (considering the present case): nasal obstruction (56.25%), epistaxis (56.25%), facial pain (25%) and headache (25%). [1][2][3][4][6][7][8][9][10][11][12][13] Comparing literature data, we observed that the most frequent location of the vascular leiomyoma in the nasal cavity has been in the inferior turbinate. Of the 15 cases described (Table 1), 5 originated in the inferior turbinate; and as to symptoms, the initial complaint was nasal bleeding.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…1 According to the literature, the most common symptoms are (considering the present case): nasal obstruction (56.25%), epistaxis (56.25%), facial pain (25%) and headache (25%). [1][2][3][4][6][7][8][9][10][11][12][13] Comparing literature data, we observed that the most frequent location of the vascular leiomyoma in the nasal cavity has been in the inferior turbinate. Of the 15 cases described (Table 1), 5 originated in the inferior turbinate; and as to symptoms, the initial complaint was nasal bleeding.…”
Section: Discussionmentioning
confidence: 80%
“…In both cases, the neoplasia seem to develop from the vessels' smooth muscle. 11 Vascular leiomyomas are made up of bundles of relatively organized smooth muscle cells, permeated by thick walled vessels. The surface lesions are made mainly by thick wall vessels associated with proliferative muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations